Acid rain-dependent detailed leaching characteristics and simultaneous immobilization of Pb, Zn, Cr, and Cd from hazardous lead-zinc tailing. (15th August 2022) - Wang, Haojie; Ju, Chenxuan; Zhou, Min; Chen, Jiaao; Kan, Xiaoqing; Dong, Yiqie; Hou, Haobo
Abstract: In acidic medium, hazardous heavy metals of lead-zinc tailing (LZT) are easily leachable and mobilizable. Thus, the hazard, amount, form, and complexity of the leached heavy metals under acidic precipitation become a major environmental concern. This work investigates the gangue minerals, toxicity, speciation, leaching characteristics of heavy metals in LZT under simulated acid rain, as well as immobilization effects and mechanisms using a sustainable binder. In LZT, dolomite, quartz, calcite, and muscovite are the main gangue minerals, tiny hazardous metallic minerals were absorbed in the surface. The results revealed that Pb, Zn, Cr, and Cd were the predominant harmful elements, particularly Pb and Zn. Zn is leached completely and is the concerned hazardous element under simulated acid rain. In the acid rain neutralization ability test, the amount of leachable Pb, Cr, Ca, and Si maintained in equilibrium, leached Zn, Cd, Al, and Mg depended on the addition of acid. Pb and Ca were sedimented in residues. Immobilization of Pb, Zn, Cr, and Cd depended on the stability of Ca(OH)2 /C–S–H of hydrates, and 70% LZTHP after curing 7 days can be used for some practical engineering projects. This work opens up deeply understandings for the leached heavy metals under acidic precipitation and improves the sustainable and safe in the field of immobilization of heavy metals. Graphical abstract: Image 1 Highlights: Hazardous metallic minerals were absorbed in the gangue minerals. High proportion of acid-extractable fraction causes the easily leaching of Pb, Zn, Cr, Cd. Zn is the concerned hazardous element under simulated acid rain condition. Immobilization of Pb, Zn, Cr, and Cd depended on the stability of Ca(OH)2 /C–S–H.